2015
DOI: 10.3991/ijim.v9i2.4411
|View full text |Cite
|
Sign up to set email alerts
|

Influences on the Adoption of Mobile Learning in Saudi Women Teachers in Higher Education

Abstract: Abstract-Although mobile devices are ubiquitous on university campuses, teacher-readiness for mobile learning has yet to be fully explored in the non-western nations. This study shows that two main factors affect the adoption and use of m-learning among female teachers within a university in Saudi Arabia-resistance to change and perceived social culture. These determinants of the current use and intention to use of m-learning were revealed through the analysis of an online questionnaire completed by 165 female… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 8 publications
2
20
0
1
Order By: Relevance
“…He further estimated that in 2017, these revenues would be more than double, to reach $205.4 million, with a proximate growth rate of 18.4 %. Alfarani (2015) argued that the number of students who uses mobile devices as educational resources will continue to rise sharply in Saudi Arabia.…”
Section: Significance Of the Studymentioning
confidence: 99%
See 1 more Smart Citation
“…He further estimated that in 2017, these revenues would be more than double, to reach $205.4 million, with a proximate growth rate of 18.4 %. Alfarani (2015) argued that the number of students who uses mobile devices as educational resources will continue to rise sharply in Saudi Arabia.…”
Section: Significance Of the Studymentioning
confidence: 99%
“…Regarding the use of mobile phones, in the United States , the number of mobile phones users was more than 200 million in (Leo, 2006. M-learning is in an early period of its implementation in the Saudi Arabia, with the decision to formally adopt m-learning in Saudi universities being a very recent one (Alfarani, 2015) . People around the globe have integrated mobile technology into their daily lives.…”
Section: Significance Of the Studymentioning
confidence: 99%
“…Aspects that should be taken into account are: (1) aspects of the device that refer to the physical characteristics, technical, and functional from mobile devices (Lee et al, 2015;Looi et al, 2015); (2) aspects of learners including the individual cognitive abilities, memory, knowledge, emotions, and perhaps motivation. This aspect explains how students use what they already know and how they encode, store, and transfer information (Kent et al, 2016;Hasyim et al, 2015); and (3) the social aspect associated with and explain the process of social interaction and cooperation (Sung et al, 2015;Alfarani, 2015;Brown and Mbati, 2015): while someone joining a new community, he must share the customs and culture of their own and learned people of the new community.…”
Section: Literature Reviewmentioning
confidence: 99%
“…By using this new model, it can be developed a variety of mobile learning strategies and approaches that can drive the success of learning (Anders, 2015;Jansen et al, 2015;Furió et al, 2015). Some research reports showed the success of mobile technology implementation on learning in many countries, such as Malaysia (Gan and Balakrishnan, 2016), Taiwan (Chen, 2015), Saudi (Alfarani, 2015), Oman (Sarrab et al, 2015), Ghana (Grimus and Ebner, 2015), and Europe (Jansen et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The ubiquity of mobile technology makes it a valuable tool to access online learning resources anytime, anywhere. Mobile learning is defined as a learning medium that allows learners to use mobile devices to search and obtain learn-issues that significantly affect the adoption of m-learning [16]. Another study by [17] investigated instructors' perceptions of mobile learning and mobile examination systems in some Arab countries.…”
Section: Introductionmentioning
confidence: 99%